As Tres danzas concertantes de Leo Brouwer: elementos estruturadores da sua escrita musical - Strauss, Gabriel Nogueira Batista (2019)
he present research investigates the first compositional period of Leo Brouwer, the Nationalism. Such a moment is little focused by academics and we understand it as central to understanding Brouwer's musical foundations. After going through the three creative phases of the Maestro, we find, in his initial stage, authentic compositional procedures that perpetuate themselves throughout his compositional trajectory. Thus, this dissertation is intended to investigate such elements and their unfolding along the following two compositional stages. We divide our study into four parts: the first explores the composer's three periods, for a better idiomatic understanding of the brouwerian composition. Later, based on the interview made to the composer, we looked at the first period, where Brouwer emphasized the aural influence of Afro-Cuban ritual music and the spoken Yoruba language - we dedicate two sub-chapters to these respective topics. The third is made by a description and a study of the thematic organization of the Tres Danzas Concertantes, in which we investigate the structuring elements of the work. From this stage of the research we believe to extract the main resources that ground Brouwer’s Nationalism. Finally, a fourth chapter exposes the prospections of the found elements of Tres Danzas Concertantes, in works of the two later compositional moments.